STRATEGI MENGAJAR GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA - Ni Putu Maya Widariyanti; Putra, I Gede Dimas Aditya; Sutha, I Gede Ngurah Bhisama; I Wayan Rudiarta (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Student learning interest is one of the keys that affects the success of the learning process. Students who have an interest in a material will tend to be more actively involved in the learning process. Therefore, it is important for educators to understand and develop strategies that can increase students' interest in learning. One strategy that is often used in the learning process is the expository strategy. This research examines the role of teaching strategies in increasing students' interest in learning with a focus on Hindu Religious Education at SMPN 14 Mataram. It aims to analyse the learning approach applied by Hindu teachers at SMPN 14 Mataram in an effort to increase students' interest in learning. This study uses a qualitative approach, data collected by in-depth interviews, observation, and document analysis involving one teacher and five students. The results show that the use of expository strategies complemented by methods such as lectures and question and answer effectively fosters a conducive learning environment. These methods not only actively engage students and also motivate them to better understand the material. This research highlights the importance of varied teaching approaches and effective classroom management techniques, including mutual agreement, ice-breaking activities and positive feedback. In addition, the use of visual media and real-life examples significantly improved students' understanding and interest in learning. The findings emphasise the need for continuous development of innovative teaching strategies to meet the diverse needs of students, ultimately improving learning outcomes. Keywords: Expository Strategy, Learning Interest, Students